2022
DOI: 10.1002/eap.2552
|View full text |Cite
|
Sign up to set email alerts
|

Riparian buffers made of mature oil palms have inconsistent impacts on oil palm ecosystems

Abstract: Expansion of oil palm has caused widespread declines in biodiversity and changes in ecosystem functioning across the tropics. A major driver of these changes is loss of habitat heterogeneity as forests are converted into oil palm plantations. Therefore, one strategy to help support biodiversity and functioning in oil palm is to increase habitat heterogeneity, for instance, by retaining forested buffers around rivers when new plantations are established, or maintaining buffers made of mature oil palms (“mature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 93 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…It is likely that lower N 2 O emissions from areas with buffer treatments could potentially offset large N 2 O fluxes related to N fertilisation rates in surrounding plantation areas and hence lower the GHG footprint of the plantation as a whole (Pardon et al, 2016;Meijide et al, 2020;Skiba et al, 2020;Drewer et al, 2021b;Chen et al, 2023). Given the proven benefits of more complex understory vegetation for biodiversity and healthy ecosystem functioning (Ashton-Butt et al, 2018;Luke et al, 2019a;Pashkevich et al, 2022), plus the potential for restored riparian buffers to support a range of species and services (Luke et al, 2019b), and to increase their capacity for GHG emissions reductions over time, our findings therefore support the view that these features bring environmental benefits in oil palm landscapes. We recommend that future investigations of GHG emissions from plantations consider the longer-term impact of management activities, and either return to sites such as those in this study, or design experimentation that investigates emission over several years.…”
Section: Management Zones (Inside/outside Weeding Circles)mentioning
confidence: 99%
“…It is likely that lower N 2 O emissions from areas with buffer treatments could potentially offset large N 2 O fluxes related to N fertilisation rates in surrounding plantation areas and hence lower the GHG footprint of the plantation as a whole (Pardon et al, 2016;Meijide et al, 2020;Skiba et al, 2020;Drewer et al, 2021b;Chen et al, 2023). Given the proven benefits of more complex understory vegetation for biodiversity and healthy ecosystem functioning (Ashton-Butt et al, 2018;Luke et al, 2019a;Pashkevich et al, 2022), plus the potential for restored riparian buffers to support a range of species and services (Luke et al, 2019b), and to increase their capacity for GHG emissions reductions over time, our findings therefore support the view that these features bring environmental benefits in oil palm landscapes. We recommend that future investigations of GHG emissions from plantations consider the longer-term impact of management activities, and either return to sites such as those in this study, or design experimentation that investigates emission over several years.…”
Section: Management Zones (Inside/outside Weeding Circles)mentioning
confidence: 99%
“…Ditjen Perkebunan (2011) reported that about 20 percent of Indonesian OP plantations were located in peatland areas. Compared to other crops, a wellmanaged OP plantation could also support a complex ecosystem that harbors relatively high biodiversity (Koh, 2008;Hood et al, 2020;Pashkevich et al, 2022).…”
Section: Introductionmentioning
confidence: 99%